Aktivitas Antibakteri Fraksi Allium ascalonicum Linn A562275sal Lembah Palu terhadap Shigella dysenteriae - Akhmad Khumaidi; Kumalahayati Maulina; Arsa Wahyu Nugrahani (Fakultas Farmasi Universitas Pancasila, 2019)
Shallot (Allium ascalonicum Linn.) is one of the typical plants of Central Sulawesi which is used as traditional medicine such as to treat infectious diseases. This study aims to determine the fractions that have high activity from bulbs and leaves in inhibiting the growth of Shigella dysenteriae bacteria and determining the organic compounds that have antibacterial activities. Extraction was carried out by maceration method using ethanol 96% for both samples. Liquid-liquid fractionation was used as a fractionation method using hexane, ethyl acetate and water solvents, sequenly. The antibacterial activity test used the diffusion method with the pile technique and TLC-bioautography. The results showed that ethyl acetate fraction gave the highest activity of bulbs samples, while in leaves samples ethyl acetate fraction and hexane fraction were able to provide good inhibitory activity. The organic compounds were identified by thin layer chromatography method. Flavonoids compounds have identified for bulbs samples (Rf 0.18). In the leaves samples, steroids compounds were identified in the ethyl acetate fraction (Rf 0.62) and terpenoid compounds (Rf 0.48) in the hexane fraction. Based on the result, the shallot is potentially be developed as an antibacterial material.